Effect of different moisture cantent on the migration behaviour of LNAPL in aggregated kaolin using light reflection method - Shily, Chow Wannyen (2016)
In this research, Light Reflection Method was used to investigate the effect of different moisture content on the migration behaviour of LNAPL in aggregated kaolin. Contamination of groundwater and soil raised the concern on the migration behaviour of LNAPL to aid in remediation research. Therefore, this research was conducted to study the migration behaviour of LNAPL in double porosity media of moisture content 27 %, 29 %, 31 % and 33 %. Photographic method was used to acquire images during the experiments. Image analysis technique was applied to acquire data of research using software Image-Pro Premier 9.1. Based on the findings, LNAPL migrated at the fastest rate with the highest velocity in aggregated kaolin of 31 % moisture content due to larger inter-aggregate pore space when moisture content increased. Other than that, the area of LNAPL migration is the smallest in aggregated kaolin of 31 % moisture content due to higher residual saturation in the larger pore space. The final saturation of 31 % moisture content aggregated kaolin is the lowest due to the weaker capillary pressure in larger pore space. The mean intensity of the LNAPL migration is more uniform in aggregated kaolin of 31 % moisture content because disturbance on light intensity was greatly reduced with the shortest duration of migration. In conclusion, the effect of moisture content on migration behaviour of LNAPL in aggregated kaolin can be investigated using Light Reflection Method. Using photographic method, it has enabled the visualization on LNAPL migration behaviour in aggregated kaolin with data from image analysis.